Increasing Writing Skill of Narrative and Motivate Students Class IV Primary School Through Environment Approach - Richi Viodelf; Syahrul Syahrul; Yalvema Miaz (International Conferences on Educational, Social Sciences and Technology)
Based on early observation and teaching experience in grade IV student of SDIT Mutiara Hati Payakumbuh, finding writing skill of narrative in grade IV is low. For that need to improvement for help student in writing of narrative by correct stage. The research purpose to explain the process, result and motivate of learning writing skill by environment approach. The kind of the research is class action research through environment approach. Based on the result of research, using environment approach in learning writing student skill of narrative proved can increase writing skill of student. Increasing average in result of learning at pre cycle student writing skill of narrative by average 69,82 %. After did action increase skill become 80,5% at phase II student writing skill increase become 87,5%, writing of narrative through environment approach proved can motivate student by result of questionnaire by student, as many 58,3% student always want to study by environment approach and around 29,2 % hope more after study through environment approach.